De Gaulle - Crozier, Brian (Scribner, 1973)
This monumental and fascinating biography is the first full-scale portrait of one of the towering figures of the Twentieth Century. Brian Crozier describes the whole range of De Gaulle's extraordinary and controversial career, and places his achievement in the context of world history.